Bioremoval of Chromium, Copper and Cadmium by Bacillus cereus in Simulated Electroplating Wastewater - Yulinah Trihadiningrum (Institut Teknologi Sepuluh Nopember, 2014)
Heavy metal pollution is one of environmental problems, which is caused by the discharge of improperly treated industrial wastewater. Electroplating industry generates wastewater containing heavy metals, which include chromium, copper and cadmium. Biological treatment using bacteria has been considered as a new alternative for treatment of heavy metal containing wastewater. The bacteria play an important role in the bioremediation of heavy metal contaminated environment. Bacillus cereus was known as cosmopolitan bacteria with high resistance to pollutants. This study was conducted to measure the viability of two strains of Bacillus cereus in chromium, copper and zinc containing cultures, and the bioremoval efficiencies of the heavy metals.. The bioremoval efficiencies were measured using spectrophotometric method. The bacterial viability was measured according to the Optical Density of the culture. The results showed that both B. cereus strains were viable in culture containing chromium, copper, and cadmium with different concentrations. The highest tolerance of the bacteria was observed in chromium containing culture, where highest chromium bioremoval efficiency of 51.8% was performed by ATCC 9632 strain at chromium concentration of 102.4 mg/L, in varied concentration range up to 360 mg/L. Whereas the highest copper bioremoval efficiency of 100% was achieved in the cultures of B. cereus ATCC 1178 and ATCC 9632 at copper concentration of 2 mg/L in tested concentration range up to 10 mg/L. The highest cadmium bioremoval efficiency of 77% was achieved by ATCC 9632 strain at concentration of 15 mg/L in concentration range up to 25 mg/L